Under the color of law a Kevin Kerney novel - McGarrity, Michael (New York : Dutton, 2001)
Before newly installed police chief Kevin Kerney can discover who murdered a U.S. ambassador's estranged wife, the FBI takes over the investigation, and soon witnesses vanish and the case is neatly solved, but Kerney is convinced that he is in the midst of an intelligence cover-up riddled with devious government agents and must race against time to uncover the truth.
Keywords: Kerney, Kevin (Fictitious character); Police -- New Mexico -- Santa Fe; Police chiefs; Santa Fe (N.M.); Mystery fiction